Educational intervention to improve ceftriaxone prescription in an emergency department: Ceftriaxone overuse (Actualizaciones en Sida e Infectología, 2023)
Objective: To evaluate the prevalence and appropriateness of ceftriaxone after an educational intervention in an emergency department.Methods: Quasi-experimental study, which included a consecutive sampling of unscheduled consultations of adult patients, during 2 months pre-intervention and post-intervention. The intervention consisted of training physicians to limit its indication only to specific clinical situations (meningitis, pelvic inflammatory disease, and acute abdomen). Retrospective data were used, with additional manual chart review, to validate appropriateness of antibiotic initiation and drug appropriateness. Descriptive and analytical statistics were used.Results: Among 28570 visits, 512 received ceftriaxone (1.79%; 95%CI 1.64-1.95), and only 60.54% were hospitalized. Regarding the before-after comparison, we observed a reduction in the rate of use (from 3.66% to 0.63%; p
Keywords: Emergency Service, Hospital; Practice Patterns, Physicians'; Ceftriaxone; Health Care Costs; Drug Resistance, Bacterial